Double-ramp on the Main Himalayan Thrust revealed by broadband waveform modeling of the 2015 Gorkha earthquake sequence - Wang, Xin (2018)
The 2015 Mw 7.8 Gorkha earthquake sequence that unzipped the lower edge of the Main Himalayan Thrust (MHT) in central Nepal provides an exceptional opportunity to understand the fault geometry in this region. However, the limited number of focal mechanisms and the poor horizontal locations and depths of earthquakes in the global catalog impede us from clearly imaging the ruptured MHT. In this study, we generalized the Amplitude Amplification Factor (AAF) method to teleseismic distance that allows us to model the teleseismic P-waves up to 1.5 Hz. We used well-constrained medium-sized earthquakes to establish AAF corrections for teleseismic stations that were later used to invert the high-frequency waveforms of other nearby events. This new approach enables us to invert the focal mechanisms of some early aftershocks, which is challenging by using other long-period methods. With this method, we obtained 12 focal mechanisms more than that in the GCMT catalog. We also modeled the high-frequency teleseismic P-waves and the surface reflection phases (pP and sP) to precisely constrain the depths of the earthquakes. Our results indicate that the uncertainty of the depth estimation is as small as 1–2 km. Finally, we refined the horizontal locations of these aftershocks using carefully hand-picked arrivals. The refined aftershock mechanisms and locations delineate a clear double-ramp geometry of the MHT, with an almost flat décollement sandwiched in between. The flat (dip ∼7 degrees) portion of the MHT is consistent with the coseismic rupture of the mainshock, which has a well-constrained slip distribution. The fault morphology suggests that the ramps, both along the up-dip and down-dip directions, play a significant role in stopping the rupture of the 2015 Gorkha earthquake. Our method can be applied to general subduction zone earthquakes and fault geometry studies.